Macroprocess 04 Institutional and Diplomatic Relations - Organizational Design Division (2020)
The Macroprocess 04 Institutional and Diplomatic Relations aims to " Develop and strengthen diplomatic and institutional relations that enable IICA to carry out the mandates of its governing bodies, manage public-private sector partnerships, and pave the way for growing access to external resources.". Scope: Hemispheric level. Technical and regulatory actions. Centralization at strategic levels and at Headquarters. Decentralization at the tactical and operational level by region and country.